Clinical and economic outcomes associated with treatment sequences in patients with BRAF-mutant advanced melanoma. (19th December 2018) - Tarhini, Ahmad; McDermott, David; Ambavane, Apoorva; Gupte-Singh, Komal; Aponte-Ribero, Valerie; Ritchings, Corey; Benedict, Agnes; Rao, Sumati; Regan, Meredith M; Atkins, Michael
Aim: The cost–effectiveness of treatment sequences in BRAF -mutant advanced melanoma.Materials & methods: A discrete event simulation model was developed to estimate total costs and health outcomes over a patient's lifetime (30 years). Efficacy was based on the CheckMate 067/069 trials and a matching-adjusted-indirect comparison between immuno-oncology and targeted therapies. Safety, cost (in US dollars; US third-party payer perspective) and health-related quality-of-life inputs were based on published literature.Results: Estimated survival gain was higher for sequences initiating with anti-PD-1 + anti-CTLA-4 than for anti-PD-1 monotherapy or BRAF+MEK inhibitors. The incremental cost–effectiveness ratio per QALY gained for first-line anti-PD-1 + anti-CTLA-4 was US54, 273 versus first-line anti-PD-1 and 79, 124 versus first-line BRAF+MEK inhibitors.Conclusion: Initiating treatment with anti-PD-1 + anti-CTLA-4 was more cost–effective than initiation with anti-PD-1 monotherapy or BRAF+MEK inhibitors.